The Spatial Impacts of Rapid Urbanization on the Limited Surface Water Resources in Istanbul - Mehmet Kucukmehmetoglu; Abdurrahman Geymen (European Regional Science Association (ERSA), 2006)
In the second half of the 20th Century, during which Turkey has experienced rapid industrialization and urbanization, Istanbul has been the destination of influx of large scale rural to urban migrants. Between 1950 and 2000, the city has grown by an average of 4.5% annually. The city has been the preferred destination not only by large numbers of low skilled rural migrants who seek employment in various informal sectors, but also by capital owners looking for a large scale cheap labor source and an extensive local market. Besides, Istanbul provides a relatively well established basic infrastructure (e.g. transportation and services) compared to the rest of Turkey. Given the scale of the growth, neither local nor the central governments have shown capability of controlling the influx of migration, most of which settled illegally on public lands creating low quality low cost housing and industrial environments. Most of the settlements lack the basic sewerage facilities, and a significant portion of which are on the major water resources basins. As of today, the Municipality of Istanbul not only has to cope with the infrastructure problems, but also has to find ways of solving the problem of illegal occupations of public lands and water resource basins. This paper presents the land use changes in the water resources basins providing water to the Istanbul Metropolitan Area. Using four consecutive Landsat images between 1990 and 2005, the changes in 12 different land use categories are obtained via overlay operations by GIS for 12 major water resources basins surrounding the city of Istanbul. It has been observed that the most critical land use changes are in the nearest basins to the city. It has also been observed that large public capital improvement projects such as Trans-European Motorway (TEM) triggered the trend of illegal occupation of these public lands most of which is in the water resources basins. The capability of Landsat images in determining the alterations in the macro form of the city are also discussed. Finally, possible policy implications are put forward for the preservation of water resources basins in Istanbul.
Keywords: 330